2015
DOI: 10.1109/jphotov.2015.2392939
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Busbars in Large-Area IBC Solar Cells by Distributed SPICE Simulations

Abstract: In this paper, we model a large-area high-efficiency interdigitated back-contact (IBC) solar cell by means of a distributed electrical network. The simulation tool allows accounting for the distributed resistive effects in diffusions and metallization. The model also considers the electrical shading effect and resistive losses due to both back-surface field (BSF) and emitter busbars. A calibrated model is used to investigate the case of a large-area (15.6 × 15.6 cm2) IBC cell, in which we investigate the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Moreover, SPICE was also qualified for the modeling of thin‐film solar modules . Numerous research studies have shown that SPICE is highly competent as a simulation tool for the analyses of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SPICE was also qualified for the modeling of thin‐film solar modules . Numerous research studies have shown that SPICE is highly competent as a simulation tool for the analyses of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In FFE IBC solar cells, the holes generated in the region above BSF move to the nearest FFE, then laterally transport in the FFE, and finally reach the back emitter [8]. There is a lot of research work about the IBC solar cells with the FSF structure; however, the work about FFE IBC solar cells is relatively less abundant [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The Quokka simulation represents one unit cell of half an emitter finger and half a BSF finger, resulting in an efficiency of 23.0%. The post processing is done with analytical expressions, similar to what we previously reported , and takes into account resistive losses in the metal fingers and metal busbars and losses related to the doped Si regions above the busbars. This is summarized in Figure , where the simulated cell efficiency is shown, as a function of the busbar width, with variations in the number of busbars (6, 8 or 10), and the number of contact pads per busbar (in the range from 4 to 16).…”
Section: Cell‐module Co‐designmentioning
confidence: 99%